Advancing strength and counteracting embrittlement by displacive transformation in heterogeneous high-entropy alloys containing sigma phase. (1st March 2023) - Lu, Wenjun; Guo, Wenqi; Wang, Zhangwei; Li, Jianjun; An, Fengchao; Dehm, Gerhard; Raabe, Dierk; Liebscher, Christian H.; Li, Zhiming
Abstract: Metallic alloy design for room temperature applications typically aims at avoiding undesired brittle intermetallic phases. In transition metal alloys, the sigma phase is particularly known as a harmful phase leading to serious embrittlement. Here, we develop a novel strategy that utilizes displacive transformation and heterogeneous structures to mitigate the embrittlement of sigma phase particles in high-entropy alloys (HEAs). A careful study of the deformation behavior reveals that the displacive transformation from face-centered cubic (FCC) to hexagonal close packed (HCP) phase can effectively suppress the propagation of microcracks originated in these brittle sigma particles (310±52 nm) and contributes to high work hardening behavior during tensile deformation. This is achieved by tuning the stacking fault energy of the FCC matrix by reducing the Ni content to promote transformation induce plasticity (TRIP) around the sigma phase in a non-equiatomic Fe34 Mn20 Co20 Cr20 Ni6 (at. %) HEA. Such TRIP effect can be optimized in various heterogeneous structures with bimodal grain sizes via simple cold-rolling (∼60%) and subsequent annealing (30 min at 700 or 800 °C). The heterogeneously structured HEAs containing brittle sigma particles exhibit ultimate tensile strengths as high as ∼1.2 GPa while maintaining a ductility up to ∼50%. This is mainly attributed to the transformation induced stress-relaxation around the regions containing brittle sigma particles. The insights provide a new design strategy of combining TRIP effect and heterogeneous structures for developing strong and ductile alloys. Graphical Abstract: Image, graphical abstract